Prognostic value of PD-1, PD-L1 and PD-L2 deserves attention in head and neck cancer - Jiang, Siqing; Li, Xin; Huang, Lihua; Xu, Zhensheng; Lin, Jinguan (Frontiers in Immunology, 2022)
Head and neck cancer has high heterogeneity with poor prognosis, and emerging researches have been focusing on the prognostic markers of head and neck cancer. PD-L1 expression is an important basis for strategies of immunosuppressive treatment, but whether it has prognostic value is still controversial. Although meta-analysis on PD-L1 expression versus head and neck cancer prognosis has been performed, the conclusions are controversial. Since PD-L1 and PD-L2 are two receptors for PD-1, here we summarize and analyze the different prognostic values of PD-1, PD-L1, and PD-L2 in head and neck cancer in the context of different cell types, tissue localization and protein forms. We propose that for head and neck cancer, the risk warning value of PD-1/PD-L1 expression in precancerous lesions is worthy of attention, and the prognostic value of PD-L1 expression at different subcellular levels as well as the judgment convenience of prognostic value of PD-1, PD-L1, PD-L2 should be fully considered. The PD-L1 evaluation systems established based on immune checkpoint inhibitors (ICIs) are not fully suitable for the evaluation of PD-L1 prognosis in head and neck cancer. It is necessary to establish a new PD-L1 evaluation system based on the prognosis for further explorations. The prognostic value of PD-L1, PD-L2 expression in head and neck cancer may be different for early-stage and late-stage samples, and further stratification is required.